Current evidence for the use of N‐acetylcysteine following liver resection. Issue 6 (13th November 2017) - Kemp, Richard; Mole, Jonathan; Gomez, Dhanny; ,
Abstract : Background: N ‐acetylcysteine (NAC) has many uses in medicine; notable in the management of paracetamol toxicity, acute liver failure and liver surgery. The aim of this review was to critically appraise the published literature for the routine use of NAC in liver resection surgery. Methods: An electronic search was performed of EBSCOhost (Medline and CINAHL database), PubMed and the Cochrane Library for the period 1990–2016. MeSH headings: 'acetyl‐cysteine', 'liver resection' and 'hepatectomy' were used to identify all relevant articles published in English. Results: Following the search criteria used, three articles were included. Two of these studies were randomized controlled trials. All the studies collated data on morbidity and mortality. All three studies did not show a significant difference in overall complications rates in patients that underwent hepatic resection that had NAC infusion compared with patients that did not. In one study, NAC administration was associated with a higher frequency of grade A post‐hepatectomy liver failure. In another study, a significantly higher incidence of delirium was observed in the NAC group, which led to the trial to be terminated early. Conclusion: The current published data do not support the routine use of NAC following liver resection.